Implementasi Metode Coaching dalam Supervisi Akademik - Juhadira, Juhadira; Hasniati, Hasniati; Ririk, Ririk; Lilianti, Lilianti; Nasir, Nasir (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2024)
This study investigates the impact of coaching methods in academic supervision on the improvement of teacher performance and educational quality in schools (Location: Al-Kautsar Kindergarten, Kartika XX-46 Kindergarten Kendari, Dian Ekawati Kindergarten, and Setara Kids Kindergarten). Through interviews, direct observations, and document analysis, the research reveals that coaching serves not only as a feedback tool but also fosters deep relationships and encourages effective two-way communication between school principals and teachers. Direct observation results indicate that teachers engaged in coaching show increased motivation, self-confidence, and tangible changes in teaching practices. Document analysis supports these findings by identifying measurable changes in teaching practices through the implementation of strategies acquired through coaching. These findings align with previous research literature that emphasizes the effectiveness of coaching in the professional development of teachers and the enhancement of learning quality. In conclusion, coaching methods in academic supervision are not just strategies but a holistic approach that brings positive and measurable impacts on teacher performance and the achievement of educational goals in schools.